2015
DOI: 10.1038/ncomms8461
|View full text |Cite
|
Sign up to set email alerts
|

Printable elastic conductors with a high conductivity for electronic textile applications

Abstract: The development of advanced flexible large-area electronics such as flexible displays and sensors will thrive on engineered functional ink formulations for printed electronics where the spontaneous arrangement of molecules aids the printing processes. Here we report a printable elastic conductor with a high initial conductivity of 738 S cm−1 and a record high conductivity of 182 S cm−1 when stretched to 215% strain. The elastic conductor ink is comprised of Ag flakes, a fluorine rubber and a fluorine surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
762
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 735 publications
(765 citation statements)
references
References 42 publications
2
762
0
1
Order By: Relevance
“…Table 1 summarizes the recent advances in stretchable interconnect technology. [12][13][14][15][16] In order to realize highly flexible or stretchable backplanes based on the engineered substrate systems, further study on stretchable interconnects should be conducted. Another advantage of engineered substrates is the exclusion of a transfer process.…”
Section: Research At Unist Display Centermentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the recent advances in stretchable interconnect technology. [12][13][14][15][16] In order to realize highly flexible or stretchable backplanes based on the engineered substrate systems, further study on stretchable interconnects should be conducted. Another advantage of engineered substrates is the exclusion of a transfer process.…”
Section: Research At Unist Display Centermentioning
confidence: 99%
“…Someya and coworkers have presented stretchable organic thinfilm transistor (OTFT) backplanes on the engineered substrates. 12,17 The OTFT backplanes exploited the engineered substrates and stretchable interconnects, which consisted of silver flakes embedded in elastomer (Fig. 3b).…”
Section: Research At Unist Display Centermentioning
confidence: 99%
“…Ways to gradually change material stiffness would be effective in minimizing the risk of strain-induced mechanical failures. [87][88][89][90] The last issue is the importance of developing fl exible passive elements that are compatible with processes used on ultrathin fi lms. Circuits for wireless data transmission and power transmission need inductive or capacitive elements.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…The conventional technologies such as meander metal wiring and conductive fibers are limited in stretchability. It was reported that conductive printed paste showed 100% elongation, [4] however, it shows high resistivity and resistance variation which depends on the shape of itself. Figure 1 illustrates the configuration of the stretchable wiring that we propose.…”
Section: Introductionmentioning
confidence: 99%